Strategies for Abating Intercultural Noise in Interpreting - Chen, Jing (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2007)
AbstractThe nature of interpreting and the task it fulfills decide that it is an intercultural communicative act. There are two types of intercultural noise disturbing the communication process, that originating from the information sent by the source-language speaker, and that coming from the social, cultural and situational context of the communication process. Intercultural noise impedes the interpreting process and debases the quality of interpreting. If the ideal function of an interpreter is to ensure smooth communication between the primary parties, then his role is to remedy any potential intercultural noise in the channel. This paper then aims to formulate concrete intercultural noise-reducing strategies, which include long-term strategies, pre-interpreting strategies and during-interpreting strategies.